EFEK EKSTRAK ETANOL DAUN Chromolaena odorata L. TERHADAP KESEMBUHAN LUKA INSISI PADA TIKUS SPRAGUE DAWLEY - , drh NI SRI YULIANI, drh. Sitarina Widyarini, MP., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Chromolaena odorata is a species of weed utilized as traditional medicine especially for wound healing. The content of the active compounds of flavonoids, saponins, tannins, phytat, and cyanogenic glycosides present in the plants can be applied to in vitro wound healing. This research was conducted to study the effects of ethanol extract of C. odorata leaves at the concentration of 5%, 10%, and 20% on the healing of incision wounds in Sprague-Dawley rats. The systematics of C. odorata leaves, obtained from Timor Island (East Nusa Tenggara), were determined at Plant Taxonomy Laboratory, the Faculty of Biology, Gadjah Mada University, and extracted with 96% of ethanol. A total of 45 males of Sprague Dawley rats aged 6 weeks, weighing 150-200g, were utilized in this study. All groups of rats were given a linear incision of 3 cm long at dermal depth on the backs. K1 was treated by ointment basis, K2 by 10% of betadin, K3 by 5% of C. odorata extract, K4 by 10% of C. odorata extract, and K5 by 20% of C. odorata extract. The extract and medication were topical applied once a day at the amount of 100 mg for ten days. Then, 3 rats of each group were euthanized in day 2, 6, and 10 after incision. Subsequently, skin tissue was obtained and fixated in 10% of formalin buffer for HE and immunohistochemical staining with an antibody of VEGF and COX-2. Research design employed in this study was nested design with observed variable was macroscopic wound healing on day 0 â 10 after incision. Macroscopic wound healing process in all groups began with haemostasis and scab formation, and then the wounds were completely healed on day 4 after incision. Based on the microscopic observations